The configuration of the contentious administrative jurisdiction as a system of administrative justice in Latin-American comparative law - Brewer-Carías, Allan R. (2020)
This article has the purpose of analyzing, in the Latin American comparative administrative law, the process of configuration of the Contentious Administrative Jurisdiction as a System of Administrative Justice, which results from the progressive extension of the contentious administrative processes in order to guaranty the judicial effective protection against the Administration; the progressive extension of the concept of Public Administration and its actions as object of control; as well as the reinforcement of the constitutional right to access to justice making flexible the rules of standing and previous exhaustion of the administrative recourses in order to access the Jurisdiction.